Catheter-tract metastases associated with chronic indwelling pleural catheters. - Janes, S; Rahman, N; Davies, R; Lee, Y (2007)
Indwelling pleural catheters are increasingly being used for ambulatory treatment of malignant pleural effusion, particularly for patients unsuitable for pleurodesis. These catheters are often left in situ for the rest of the patient's life. Tumor metastasis along the tract between pleura and skin surface is a potential complication in patients with chronic indwelling pleural catheters that has seldom been reported. We describe four cases of catheter-tract metastasis that developed between 3 weeks and 9 months after catheter insertion. Catheter-tract metastasis occurred in two patients with mesothelioma despite prophylactic irradiation at time of insertion, and in two patients with metastatic adenocarcinoma. All cases were successfully treated using external-beam radiotherapy without necessitating catheter removal. A retrospective audit in our center showed that catheter-tract metastasis occurred in 6.7% of 45 patients treated with indwelling pleural catheters for malignant pleural effusions. Both clinicians and patients should be aware of this potential complication.